Андрогенодефіцитний стан у чоловіків, хворих на цукровий діабет 2 типу - Luchytskyy, V.Ye. (Ендокринологія | Endokrynologia, 2012)
Андрогенодефіцитний стан у чоловіків, хворих на цукровий діабет 2 типу